Religious Moderation as Living Islamic Law: A Maqāṣid Perspective in Indonesia and Brunei Darussalam - Muslich Shabir; Maskur Rosyid; Harapandi Dahri; Mustla Sofyan Tasfiq (Faculty of Sharia and Law, Universitas Islam Negeri (UIN) Walisongo Semarang, 2026)
Religious moderation has become an important discourse in contemporary Islamic legal studies, particularly in responding to extremism and the dynamics of religiosity in pluralistic societies. This study aims to analyze religious moderation as living Islamic law in Indonesia and Brunei Darussalam using the perspective of maqāṣid al-sharī‘a as an analytical framework. This study uses a qualitative approach through analysis of policy documents and Islamic legal literature in Indonesia as well as in-depth interviews with religious authorities and academics in Brunei Darussalam. The results show that religious moderation operates as a normative and institutional practice in the social, legal, and policy spheres. In Indonesia, religious moderation functions as a public legal ethic that integrates Islamic values ​​within a pluralistic national legal system, while in Brunei Darussalam, religious moderation acts as an institutional principle that guides the gradual and proportional implementation of Islamic law. This research offers a novelty in the form of a comparative perspective that positions religious moderation as a living Islamic law that bridges normative Islamic legal theory with institutional practice, while also proposing a maqāṣid-based framework that ensures Islamic law remains contextual, balanced, and oriented towards public welfare.